2015
DOI: 10.1038/nature15367
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil ageing is regulated by the microbiome

Abstract: Blood polymorphonuclear neutrophils provide immune protection against pathogens but also may promote tissue injury in inflammatory diseases1,2. Although neutrophils are generally considered as a relatively homogeneous population, evidence for heterogeneity is emerging3,4. Under steady-state conditions, neutrophil heterogeneity may arise from ageing and the replenishment by newly released neutrophils from the bone marrow5. Aged neutrophils up-regulate CXCR4, a receptor allowing their clearance in the bone marro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
736
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 656 publications
(778 citation statements)
references
References 35 publications
38
736
0
4
Order By: Relevance
“…Indeed, the phenotype and behavior of mature, aged neutrophils is not the same as young, newly released circulating neutrophils, even in tumor-free mice 76 . One explanation for the difference between immature and mature neutrophil function may be their distinctive composition of granules, because granules are synthesized at specific stages of neutrophil development 12 (Figure 1).…”
Section: Neutrophil Retention and Release From Bone Marrowmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the phenotype and behavior of mature, aged neutrophils is not the same as young, newly released circulating neutrophils, even in tumor-free mice 76 . One explanation for the difference between immature and mature neutrophil function may be their distinctive composition of granules, because granules are synthesized at specific stages of neutrophil development 12 (Figure 1).…”
Section: Neutrophil Retention and Release From Bone Marrowmentioning
confidence: 99%
“…An example of this was shown in mice with chemically induced cancer crossed with histamine-deficient mice, where the lack of histamine stalled differentiation of immature neutrophils and increased tumor incidence and growth 75 . These data suggest that immature cells have independent functions from mature neutrophils.Indeed, the phenotype and behavior of mature, aged neutrophils is not the same as young, newly released circulating neutrophils, even in tumor-free mice 76 . One explanation for the difference between immature and mature neutrophil function may be their distinctive composition of granules, because granules are synthesized at specific stages of neutrophil development 12 (Figure 1).…”
mentioning
confidence: 99%
“…9 Neutrophils that have resided longest in the bloodstream shed the surface selectin CD62L and enhance display of the chemokine receptor CXCR4, changes that precede extravasion and correspond with enhanced inflammatory capacity (termed neutrophil "aging"). 10,11 Simultaneously, accumulating oxidative damage and metabolic dysregulation cooperate to trigger spontaneous apoptosis among neutrophils upon their exit from the bloodstream. 12,13 Tight coordination of extravasion and cell death allows for efficient and immunologically quiescent clearance of expiring phagocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Most authors believe that neutrophil numbers remain constant with ageing, although some authors reported reduced numbers [23]. With ageing, neutrophils have been implicated in the pathogenesis of Alzheimer's disease, atherosclerosis, cancer and autoimmune diseases [23], and a role of the microbiome has been implicated recently in neutrophil ageing, with a demonstration that neutrophil proinflammatory function in vivo correlates positively with age [24]. While GM-CSF promotes the chemotaxis of neutrophils in an adult animal, this is not the case in old Fig.…”
Section: Neutrophilsmentioning
confidence: 99%